Rough draft : Cold War military manpower policy and the origins of Vietnam-era draft resistance - Rutenberg, Amy J., 1977- (Cornell University Press, 2019)
"America's inequitable system of draft deferments during the Vietnam War was the direct outgrowth of military manpower policies designed to fight the Cold War at home"--